2020
DOI: 10.1039/d0ta06455f
|View full text |Cite
|
Sign up to set email alerts
|

In operando synchrotron X-ray studies of a novel spinel (Ni0.2Co0.2Mn0.2Fe0.2Ti0.2)3O4 high-entropy oxide for energy storage applications

Abstract: This work provides various methods for understanding the mechanism of a novel spinel high-entropy oxide (Ni0.2Co0.2Mn0.2Fe0.2Ti0.2)3O4 in energy storage applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(45 citation statements)
references
References 76 publications
2
43
0
Order By: Relevance
“…Most recently, Chen's group further investigated spinel-structured (Ni 0.2 Co 0.2 Mn 0.2 Fe 0.2 Ti 0.2 ) 3 O 4 as an anode. 30 They observed that Ti ions still stayed in the spinel structure and formed LiTi 2 O 4 , which is beneficial for stabilizing the whole spinel structure and alleviating the volume change upon charging/discharging. Furthermore, the high entropy effect contributes to the uniform distribution of elements all along and tolerates mechanical stress caused by the conversion reaction.…”
Section: S R N Lnmentioning
confidence: 99%
See 1 more Smart Citation
“…Most recently, Chen's group further investigated spinel-structured (Ni 0.2 Co 0.2 Mn 0.2 Fe 0.2 Ti 0.2 ) 3 O 4 as an anode. 30 They observed that Ti ions still stayed in the spinel structure and formed LiTi 2 O 4 , which is beneficial for stabilizing the whole spinel structure and alleviating the volume change upon charging/discharging. Furthermore, the high entropy effect contributes to the uniform distribution of elements all along and tolerates mechanical stress caused by the conversion reaction.…”
Section: S R N Lnmentioning
confidence: 99%
“…Thus, the enhanced electronic and ionic conductivity contribute to the long-term cycling stability of the electrodes. Most recently, Chen’s group further investigated spinel-structured (Ni 0.2 Co 0.2 Mn 0.2 Fe 0.2 Ti 0.2 ) 3 O 4 as an anode . They observed that Ti ions still stayed in the spinel structure and formed LiTi 2 O 4 , which is beneficial for stabilizing the whole spinel structure and alleviating the volume change upon charging/discharging.…”
mentioning
confidence: 99%
“…This second phase appearance above 800 °C is also confirmed by DSC data (Figure S1b). The reported XRD analysis of entropy stabilized spinel materials is limited only to identifying the spinel phase owing to the very small crystallite sizes [16,35,36,41,46] . The detailed phase information cation distribution and structural elucidation of the entropy stabilized poses a significant challenge.…”
Section: Resultsmentioning
confidence: 99%
“…The reported XRD analysis of entropy stabilized spinel materials is limited only to identifying the spinel phase owing to the very small crystallite sizes. [16,35,36,41,46] The detailed phase information cation distribution and structural elucidation of the entropy stabilized poses a significant challenge. The observed and Reitveld refined XRD patterns of ESO-S are provided in Figure 1(c).…”
Section: Physical Characterizationsmentioning
confidence: 99%
“…27 Chen et al prepared a (Ni 1/5 Co 1/5 Mn 1/5 Fe 1/5 Ti 1/5 ) 3 O 4 ceramic with a spinel structure for energy storage applications and demonstrated that the fabricated anode material displays a high capacity (around 560 mA h g −1 ) at a current density of 100 mA g −1 and shows a superior capacity retention of 100% after 100 cycles. 28 Nguyen et al fabricated a spinel-type (Cr 1/5 Mn 1/5 Fe 1/5 Ni 1/5 Cu 1/5 ) 3 O 4 ceramic via a hydrothermal method and showed that the synthesized materials exhibit outstanding cycling stability (∼99%) after 250 cycles and superior rate capability. 29 However, it has not been exploited and utilized in the electrical fields, especially as NTC thermistor materials.…”
Section: ■ Introductionmentioning
confidence: 99%